К ВОПРОСУ О СТАТИСТИЧЕСКИХ ЗАКОНОМЕРНОСТЯХ РАЗНЫХ ФОРМ РЕЧИ НА ФОНЕТИЧЕСКОМ УРОВНЕ - Elena V. Erofeeva (Philological Studies, 2019)
The article deals with the problem of the influence of speech types (text reading and spontaneous monologue) on frequencies of local (regiolect) pronunciation features. Statistic analysis of regiolect speech reveals that text reading and spontaneous monologue as speech types distinguish from one to one in frequencies of local vowel pronunciation features («okanje», «ekanje», excessive qualitative reduction of vowels). The probability of these pronunciation features in spontaneous monologue is higher than text reading. Frequencies of consonant pronunciation features slightly depend on speech types.